2013
DOI: 10.1007/s12038-013-9386-8
|View full text |Cite
|
Sign up to set email alerts
|

White Spot Syndrome Virus infection in Penaeus monodon is facilitated by housekeeping molecules

Abstract: White Spot Syndrome Virus (WSSV) is a major pathogen in shrimp aquaculture, and its rampant spread has resulted in great economic loss. Identification of host cellular proteins interacting with WSSV will help in unravelling the repertoire of host proteins involved in WSSV infection. In this study, we have employed one-dimensional and two-dimension virus overlay protein binding assay (VOPBA) followed by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) to identify the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Sarcoplasmic calcium-binding protein is also an important allergen in the muscle and shell of Fenneropenaeus merguiensis (24). WSSV infection in Penaeus monodon is facilitated by housekeeping molecules like sarcoplasmic calcium-binding protein 1 (25). When sarcoplasmic calcium-binding protein 1 was knocked down, WSSV infection would cause the animals to die faster and more often, but in V. alginolyticus infection this would only reduce the lifespan of infected crabs but decreased the overall mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoplasmic calcium-binding protein is also an important allergen in the muscle and shell of Fenneropenaeus merguiensis (24). WSSV infection in Penaeus monodon is facilitated by housekeeping molecules like sarcoplasmic calcium-binding protein 1 (25). When sarcoplasmic calcium-binding protein 1 was knocked down, WSSV infection would cause the animals to die faster and more often, but in V. alginolyticus infection this would only reduce the lifespan of infected crabs but decreased the overall mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2+ concentration is critical in the viral life cycle (capsid transport) and influences many host cell defense responses such as apoptosis [67,68]. The down-expression of the gene scp was already observed in post-larvae of the shrimp Penaeus modon infected with WSSV [69], and was revealed by 2-DE proteomic study in the stomachs of the shrimp Penaeus vannamei challenged with WSSV [17,70]. Interestingly, the genome of OsHV-1 contains one ORF which encodes a cellular chloride ion channel (ORF 57) [71] that would allow the virus to modulate the host Ca 2+ homeostasis.…”
Section: Targeted Signaling Pathwaysmentioning
confidence: 99%
“…In addition, temperatures between 22 and 30°C increased the replication efficiency of WSSV (SUN et al, 2014) in the early stages of acute infection, which coincides with the optimum temperature range for juvenile shrimp when uninfected (RAHMAN et al, 2006). Molecular interactions between the virus and the activity of constituent genes, important for the development of Penaeus monodon, such as hsp70 and ATP synthetase, were identified; thereby, it is suggested that the WSSV benefits from the phase in which there is more development of the host (BIRADAR et al, 2013). The study of these factors becomes important to understand the cyclic episodes of infection, whether by the recurrence of the same genotype or by the introduction of new viral variants.…”
Section: Resultsmentioning
confidence: 87%